alpha-Lipoic acid modulates gut inflammation induced by trinitrobenzene sulfonic acid in rats - ERCAN, FERİHA (WILEY, 2007)
Background and Aim: alpha-Lipoic acid (ALA) has been shown to combat oxidative stress by quenching a variety of reactive oxygen species. It is involved in the regeneration of exogenous and endogenous antioxidants, chelation of metal ions, and repair of oxidized proteins. This study aimed to evaluate the potential beneficial effect of ALA on trinitrobenzenesulfonic acid (TNBS)-induced gut ileitis and colitis in rats. Method: After 48 h of fasting, Sprague-Dawley rats underwent a laparotomy under ether anesthesia. TNBS solution 30 mg/mL in 40% ethanol (1 mL) was injected into the lumen, 10 cm proximal to the ileocolonic junction to induce ileitis or intrarectally 8 cm proximal to the anal sphincter to induce colitis. ALA (25 mg/kg intraperitoneally, twice a day) was given after induction of inflammation and continued for 3 days. All animals were decapitated 3 days after induction of the inflammation. The mucosal lesions of the ileum and colon were scored macroscopically and microscopically. Samples were taken for the measurement of malondialdehyde (MDA) and glutathione (GSH) levels, tissue-associated myeloperoxidase (MPO) activity and luminol- or lucigenin-enhanced chemiluminescence (CL). Results: Macroscopic scores, morphological changes and increased tissue lipid peroxidation with a concomitant reduction in GSH of the ileitis or colitis groups were all reversed by treatment with ALA. ALA treatment was also effective in improving tissue MPO activity and CL values, which were elevated in untreated ileitis or colitis groups. Conclusion: ALA is beneficial in TNBS-induced gut inflammation in rats via suppression of neutrophil accumulation, preservation of endogenous glutathione and inhibition of reactive oxidant generation.
Keywords: alpha-lipoic acid; colitis; ileitis; rat; trinitrobenzenesulfonic acid (TNBS); REACTIVE OXYGEN; ANTIOXIDANT; MODEL; GLUTATHIONE; METABOLISM; ACTIVATION; LIPOATE; COLON